NITRATE REDUCTASE ACTIVITY OF SULPHATE-REDUCING BACTERIA Desulfomicrobium SP. CrR3 AT THE DIFFERENT CONDITIONS OF THE CULTIVATION - L. S.; T. B.; S. P. (Biotechnologia Acta, 2016)
The aim of research was to study nitrate reductase activity of sulphate-reducing bacteria Desulfomicrobium sp. CrR3 at the different conditions of cultivation. To determine nitrate reductase activity, sulphate-reducing bacteria Desulfomicrobium sp. CrR3 cultivated in a modified Postgate C medium. Nitrate reductase activity was determined at different conditions: to 15–45 °C, pH 5–9. The highest nitrate reductase activity for Desulfomicrobium sp. CrR3 was at to 25 and 35 °C and pH 7–8. Lowering or raising the temperature and pH caused the inhibition of the nitrate reductase. The highest nitrate reductase activity was found in the soluble fraction of cells (12 µmol nitrite•min-1•mg protein-1). Activity was lower in the cells debris (5 µmol nitrite•min-1•mg protein-1), while it was absent in the culture fluid. It was established that nitrate reductase of bacteria Desulfomicrobium sp. CrR3 is constitutive enzyme. The value of Km for nitrate for studied enzyme in bacteria Desulfomicrobium sp.CrR3 is 1.2 µmol, Vmax – 15.7 µmol nitrite•min-1•mg protein-1), indicating that the high affinity of the enzyme to the substrate. Thus, the cultivation conditions significantly affect the nitrate reductase activity of bacteria Desulfomicrobium sp. CrR3.